Johannishusparken - Jeschke Henriksson, Katharina (2007)
The estate of Johannishus is situated in the south of Sweden and in the province of Blekinge, about 8 kilometres from the city of Ronneby. The main building together with the park represents the province´s only example of a well preserved estate environment from the early 1800th Century, and was declared as a historic monument in 1982 because of its unique role in the province. Johannishus Park has during 300 years developed in close relation to the main building, the landscape and the surrounding infrastructure. Each century and owner has had an influence on the park, which has resulted in an interesting visible cross-section of 300 years of Swedish garden history. Most noticeable today are the traces from late 19th Century, but in its oldest parts the park contains structures from the early 18th Century. In that way the park represents an important part of the province´s oldest garden history. During the 1800th Century a large formal garden existed, which was situated south of the main building. This garden played both an aesthetic and a practical role and was divided into 8 quarters where fruit trees, vegetables and flowers grew. Trimmed hedges, pavilions and arbours (Carpinus betulus) surrounded the area and a strict system of walks gave structure to the interior of the garden. In the early 1900th Century, a landscape garden was created close to Listerby River west of the main building. Previously this place had been cultivated with cabbage and used as a large enclosed pasture ground with several fishponds. This changed into a park around 1800. The new park was developed and integrated with the natural terrain, and the water was crossed by several bridges and walks. Benches and seesaws were also placed along walkways to enhance the experience during walks. Around 1840 another park was created in the eastern part of the estate, reflecting the garden ideas of this time, arranged in a natural shape and planted with exotic threes like Pinus strobus. In 1860 this park was expanded into the surrounding fields. About 80 new individual trees were planted at that time. In 1915 the garden architect Rudolf Abelin was engaged to improve the area close to the main building. He made a plan, inspired by the Arts and Crafts movement, which was largely followed and resulted in a rectangular shaped garden close to the western facade, surrounded by strict hedges and trees in pyramid shapes. A stone pergola was also built close to the northern facade and terraces where arranged with borders. The garden of Abelin was improved with new borders in the 1930s, by Carola Wachtmeister. The ponds and the bridges in the landscape garden were restored in the 1960´s. And about that time a lot of rhododendron bushes also were planted close to the Listerby River. In 1984 a pavilion was built in the eastern park and the working houses from the 1800th century have been restored in 2004. Johannishus Park today comprises many historical values, as well as natural and recreation values. The vegetation includes many old trees and in the area a number of old structures connected to the gardens and parks can be found. Some examples are the avenues, indigenous and exotic vegetation, old stone hedges and walks. An inventory is presented in this work through plant lists, photographs, sketches and descriptions. During the last centuries large areas in the park have been affected by an aggressive growth of bushes and small trees. Above all, this is noticeable close to the Listerby River and the eastern park, but the connection with the landscape is also broken. Based on the evaluation of the values and problems identified in today's park, the thesis suggests remedial measures as well as advice for the future maintenance of the park. The measures include an emphasis on enhancing experiences of the remaining garden traces of earlier centuries, and the biological values in terms of for example birdlife.